2011
DOI: 10.1002/elps.201100283
|View full text |Cite
|
Sign up to set email alerts
|

Barcoding ofGiardia duodenalisisolates and derived lines from an established cryobank by a mutation scanning‐based approach

Abstract: We barcoded 25 in vitro isolates (representing 92 samples) of Giardia duodenalis from humans and other animals, which have been assembled by the Upcroft team at the Queensland Institute of Medical Research over a period of almost three decades. We used mutation scanning-coupled sequencing of loci in the triosephosphate isomerase (tpi), glutamate dehydrogenase (gdh) and beta-giardin (bg) genes, combined with phylogenetic analysis, to genetically characterise them. Specifically, the isolates (n = 14) of G. duode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 111 publications
0
15
0
Order By: Relevance
“…Current evidence indicates that, on a global level, assemblage B is slightly more prevalent than assemblage A in both developed and developing countries (Feng and Xiao, 2011). The only two previous studies, which analysed a small number of Giardia isolates from Queensland, identified both assemblage A and B (Nolan et al 2011;Ebner et al 2015). Analysis of genetic variability within assemblages has shown that isolates of assemblage A can be divided into four sub-assemblages (AI, AII, AIII and AIV) by protein polymorphisms of 23 loci (Monis et al 1996(Monis et al , 2003, with human isolates belonging to AI and AII and animal isolates belonged to AI, AIII and AIV (Monis et al 2003;Cacciò et al 2008;Sprong et al 2009;Ryan and Cacciò, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Current evidence indicates that, on a global level, assemblage B is slightly more prevalent than assemblage A in both developed and developing countries (Feng and Xiao, 2011). The only two previous studies, which analysed a small number of Giardia isolates from Queensland, identified both assemblage A and B (Nolan et al 2011;Ebner et al 2015). Analysis of genetic variability within assemblages has shown that isolates of assemblage A can be divided into four sub-assemblages (AI, AII, AIII and AIV) by protein polymorphisms of 23 loci (Monis et al 1996(Monis et al , 2003, with human isolates belonging to AI and AII and animal isolates belonged to AI, AIII and AIV (Monis et al 2003;Cacciò et al 2008;Sprong et al 2009;Ryan and Cacciò, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Although the SSCP‐based analyses have been used routinely in our laboratory for the detection and characterization of species and genotypes/assemblages of Cryptosporidium or Giardia , it had not been employed previously for the analysis of ITS‐2 products PCR‐amplified directly from human fecal DNA samples (rather than parasite DNA). The detection of single ITS‐2 bands on agarose gels, discrete profiles by SSCP, and unambiguous sequences resulting from selective sequencing of amplicons has inferred exquisite specificity of the PCR (determined by primer NC1).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, SSCP has found applicability because a standard protocol can be applied to a wide range of genetic markers and organisms. For instance, PCR‐based SSCP analysis of internal transcribed spacer sequences of nuclear ribosomal DNA allows the specific identification of key parasitic nematodes of major importance and nuclear genes, such as 60 kDa glycoprotein ( gp60 ) and triose phosphate isomerase ( tpi ), are commonly employed for the specific detection or characterization of protozoa, such as Cryptosporidium and Giardia . The method has been applied to DNA isolated directly from parasitic protozoans and from biological matrices, including feces.…”
Section: Introductionmentioning
confidence: 99%
“…Although a considerable amount of genetic information is available for G. duodenalis , more baseline data is required at the proteomic level for a systems biology approach to be pursued. In this study, we analyzed eight assemblage A strains of diverse origins previously characterized in the literature according to karotype , assemblage , virulence , geographic variation , and drug resistance . Of these eight strains, three are from animals (one each of wild, companion, and livestock animal) and five were isolated from human infections, including one A2 strain as well as the subassemblage A1 genome strain (full strain classification information can be found in Supporting Information Table 1).…”
Section: Summary Of Peptide and Protein Identification Data Of G Duomentioning
confidence: 99%